Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3727/096504009789735431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Relationship Between Chronic Lymphocytic Thyroiditis and Papillary Thyroid Carcinoma

Abstract: The association between chronic lymphocytic thyroiditis and papillary thyroid carcinoma has been investigated for several years from different perspectives but with few attempts to design a common frame of reference to understand the complex mutual interactions between the various pathways of inflammatory response and of thyroid tumor induction and progression. This article reviews the current knowledge and research on this topic according to epidemiologic, immunobiologic, pathologic, and biomolecular points o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 77 publications
0
31
0
4
Order By: Relevance
“…In addition to the classical HT, recent studies have proposed that IgG4-related thyroiditis may be considered as a variant of HT (2). The association between HT and PTC has been a subject of long and ongoing debate (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the classical HT, recent studies have proposed that IgG4-related thyroiditis may be considered as a variant of HT (2). The association between HT and PTC has been a subject of long and ongoing debate (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto's thyroiditis (HT) -chronic lymphocytic thyroiditis or autoimmune thyroiditis -is a well-defined clinicopathologic entity and its incidence has increased over the past 50 years (1). HT is characterized by hypothyroidism, the presence of serum antithyroglobulin and antiperoxidase antibodies, and widespread lymphocytic infiltration with depletion of follicular cells.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis and the prognosis of the coexistence of PTC and Hashimoto's thyroiditis remain controversial. But Hashimoto's thyroiditis might represent the host immune response to preexisting PTC; PTC might be induced or triggered by preexisting Hashimoto's thyroiditis, and a common mechanism, such as imbalance between apoptotic/antiapoptotic pathways, may be involved in the two diseases [26]. Previous studies have reported that chronic inflammation responses such as those associated with autoimmune thyroiditis might act as carcinogens [27] or rearranged in transformation/PTC oncogene that is known to be highly specific to PTC might be expressed in Hashimoto's thyroiditis [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some microscopic papillary carcinomas show a metastatic phenotype. In this setting autoimmune thyroiditis and papillary cancer have provided a useful model with which to examine interactions between cancer and the immune system (2).…”
Section: Introductionmentioning
confidence: 99%